The constitutional test of necessity: problem statement - A. V. Dolzhikov (Правоприменение, 2022)
The subject-matter of the research is the constitutional test of necessity. This element of proportionality could be found in doctrine and case-law in the form of metaphors. The necessity as a prong of proportionality consists in testing the available alternatives in comparison with the measures that the legislator has chosen to achieve public aims. The notion of a least restrictive means can be used as a synonym for this element of proportionality. Although this term is cumbersome, it more precisely defines the nature of constitutional litigation, where the admissibility of interference with fundamental rights is assessed.The purpose of the research is to argue that this element of proportionality implies the assessment of the least restrictive alternatives for the rights-holder in order to achieve the goal chosen by the legislator.The methodology of research includes the method of analogy. Accordingly, the analogical reasoning is used in constitutional adjudication when testing necessity of legislative measures, but not the methods of logical subsumtion or judicial balancing. The sources of such analogy can be the rules of international law, ordinary legislation and comparative legal materials.The main results of the research and the scope of their application. The expression necessity is widely used in international law and ordinary legislation. Such approaches are relevant to constitutional adjudication. Thus, the ultima ratio principle, which initially appears in criminal and administrative law, acquires universal application in constitutional justice. This criterion, which requires the use of the most severe legal measures only as a last resort, with the ineffectiveness of softer alternatives, can be extended to the constitutionalization of other branches of legislation.The test of necessity, which is often expressed in metaphors, in the case-law of constitutional justice is based on the method of analogy. In the decisions of the constitutional justice bodies, the least restrictive means are often mentioned in comparison with those which were originally chosen by the legislator. At the same time, the discovered alternatives should be equally or at least minimally suitable in comparison with the existing legislative solutions. Comparative law, international law, or ordinary legislation are often an auxiliary source for constitutional judges to identify and formulate least restrictive alternatives.Conclusions. The value of the analogical reasoning, including the appeal of constitutional justice to comparative law materials, lies in the possibility of identifying some experimental legal regimes. Moreover, the perception of specific alternatives, their clarification or modification remains within the discretionary powers of the legislature. Thus, avoiding the well-known counter-majoritarian difficulty, constitutional justice conducts a dialogue with the parliament, and in the end, contributes to the optimal implementation of fundamental rights.